2018
DOI: 10.1177/1357633x18775855
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for telehealth group-based treatment: A systematic review

Abstract: Background Interest in the use of telehealth interventions to increase access to healthcare services is growing. Group-based interventions have the potential to increase patient access to highly needed services. The aim of this study was to systematically review the available literature on group-based video teleconference services. Methods The English-language literature was searched using Ovid MEDLINE, PubMed, PsycINFO and CINAHL for terms related to telehealth, group therapy and support groups. Abstracts wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
120
0
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 170 publications
(139 citation statements)
references
References 50 publications
(232 reference statements)
10
120
0
9
Order By: Relevance
“…Our results showed how MHWs adopted remote work practices. Tele-psychiatry practices have been tested in different contexts and can be useful and effective for both psychiatric assessment and monitoring interventions [28,29], individual psychotherapy [30,31] and group interventions [32]. Online psychological support programs have been reported in several countries during the Covid-19 pandemic, including China [33], Germany [34], the United States [35], and France [36].…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed how MHWs adopted remote work practices. Tele-psychiatry practices have been tested in different contexts and can be useful and effective for both psychiatric assessment and monitoring interventions [28,29], individual psychotherapy [30,31] and group interventions [32]. Online psychological support programs have been reported in several countries during the Covid-19 pandemic, including China [33], Germany [34], the United States [35], and France [36].…”
Section: Discussionmentioning
confidence: 99%
“…The use of telepsychiatry can also be expanded to facilitate group therapy. A systematic review of the evidence for telehealth group-based treatment found video teleconference groups to be feasible and to result in similar treatment outcomes to in-person groups (Gentry et al 2019). However, the potential for small decreases in therapeutic alliances was noted.…”
Section: Telepsychiatrymentioning
confidence: 99%
“…A systematic review of group-based video teleconferencing suggested that despite its limitations, video conference group treatment is feasible and produces outcomes similar to in-person treatment, with high participant satisfaction. 13 The most common modes of treatment were health literacy education, cognitive behavioral therapyincluding coping skills and cognitive processing-and mindfulnessbased therapy, mostly for physical illness. 14 ‱ We anticipate that Telehealth will be part of the solution to improving future health service quality, delivery and access.…”
Section: Treatmentmentioning
confidence: 99%